Macromedia Flash Improves the Spirit of Teaching - Miftahudin; Afdal, Zul (P3M STKIP 'Aisyiyah Riau, 2024)
The purpose of this study is to find out how learning using project-based electronic learning can increase the teaching spirit of lecturers. The results of the research can be obtained based on the experience of lecturers whose learning uses project-based electronic learning. Then the analysis obtained was carried out in the form of qualitative analysis. In this study, learning experience is used to see the extent of lecturers in the use of electronic learning to support student projects. The results of the analysis show that the use of project-based electronic learning is proven to increase the enthusiasm of lecturers in Macro/Micro Economics courses. Based on the results of the analysis, it also show that when the enthusiasm of lecturers in delivering learning increases, the enthusiasm of students in receiving learning also indirectly increases.